Mastering the Hard Stuff: The History of College Concrete-Canoe Races and the Growth of Engineering Competition Culture. Issue 2 (4th May 2019) - Bix, Amy Sue
ABSTRACT: This article details the history of college engineering competitions, originating with student concrete-canoe racing in the 1970s, through today's multi-million-dollar international multiplicity of challenges. Despite initial differences between engineering educators and industry supporters over the ultimate purpose of undergraduate competitions, these events thrived because they evolved to suit many needs of students, professors, schools, corporations, professional associations, and the engineering profession itself. The twenty-first-century proliferation of university-level competitions in turn encouraged a trickling-down of technical contests to elementary-age children and high schools, fostering the institutionalization of what might be called a competition culture in engineering.